91. Neurophysiological evaluation of spinal excitability in patients affected by primitive restless legs syndrome. Issue 1 (January 2015) - Congiu, P.; Milioli, G.; Gioi, G.; Tacconi, P.; Fantini, M.L.; Figorilli, M.; Marrosu, F.; Parrino, L.; Puligheddu, M.
<x xml:space="preserve">Abstract</x> The aim of our study is to explore the spinal excitability through the electrophysiological evaluation of patients affected by primitives Restless Legs Syndrome (RLS). 15 women affected by primitive RLS were compared with age-matched healthy females. All subjects underwent ENG evaluation: nerve conduction studies (NCS), F waves parameters (minimum, mean and maximum latency, duration, amplitude, persistency and the ratio between F wave duration (FWD) and the duration of the corresponding compound muscle action potential (FWD/CMAPD), and the Cutaneous Silent Period parameters (latency, duration and the ratio between duration at low to upper extremities). None of the subjects included in our study showed alterations in the NCS. Compared to the control group, RLS patients showed significantly higher values of the FWD for both ulnar (p < 0.05) and tibial (p < 0.01) nerves and for the FWD/CMAPD ratio (p < 0.001). The results of our study indicate a widespread spinal motoneuronaI hyper-excitability that could be mainly due to an altered modulation within the interneuronal system. Presently, RLS diagnosis is based exclusively on clinical criteria. The FWD/CMAPD ratio can help to shed light on the pathogenesis of RLS, and can represent an objective, easily obtainable, diagnostic tool especially in cases of evening lower leg discomfort of unclear interpretation.